The effect of home-based inspiratory muscle training on exercise capacity, exertional dyspnea and pulmonary function in COPD patients - Maryam Bakhshandeh Bavarsad; Abdolali Shariati; Esmaeil Eidani; Mahmud Latifi (Wolters Kluwer Medknow Publications, 2015)
Background: Chronic obstructive pulmonary disease (COPD) is currently the fourth cause of mortality worldwide. Patients with COPD experience periods of dyspnea, fatigue, and disability, which impact on their life. The objective of this study was to investigate the effect of short-term inspiratory muscle training on exercise capacity, exertional dyspnea, and pulmonary lung function. Materials and Methods: A randomized, controlled trial was performed. Thirty patients (27 males, 3 females) with mild to very severe COPD were randomly assigned to a training group (group T) or to a control group (group C). Patients in group T received training for 8 weeks (15 min/day for 6 days/week) with flow-volumetric inspiratory exerciser named (Respivol). Each patient was assessed before and after 8 weeks of training for the following clinical parameters: exercise capacity by 6-min walking test (6MWT), exertional dyspnea by Borg scale, and pulmonary lung function by spirometry. Patients used training together with medical treatment. The data were analyzed using paired t-test and independent t-test. Results: Results showed statistically significant increase in 6MWT at the end of the training from 445.6 ± 22.99 to 491.06 ± 17.67 meters? (P < 0.001) and statistically significant decrease in dyspnea from 3.76 ± 0.64 to 1.13 ± 0.36 (P = 0.0001) in the training group but not in the control group. The values for exercise capacity and dyspnea improved after 8 weeks in group T in comparison with group C (P = 0.001 and P = 0.0001, respectively). No changes were observed in any measure of pulmonary function in both groups. Conclusions: Short-term inspiratory muscle training has beneficial effects on exercise capacity and exertional dyspnea in COPD patients.